The use of elements of neuropedagogy in the creation of virtual simulators for in-depth study of chemistry in higher education - Aiman Rakhmetova; Gulzhamila Meiirova; Didara Balpanova; Ainash Baidullayeva; Dina Nurmakhanova (OmniaScience, 2024)
This study investigates the efficacy of incorporating neuropedagogical elements into virtual simulators for advanced chemistry education in universities. Utilizing a mixed-method approach, it uses questionnaires completed by 50 organic chemistry students. These questionnaires included both general and Likert scale questions, focusing on students' experiences with the PhET Interactive Simulation. The results highlight the positive impact of neuropedagogy on students' learning attitudes, cognitive abilities, and skill development, particularly in areas like critical thinking, analytical skills, and social competencies. A significant portion of students reported enhanced educational outcomes: 76% observed improved training effectiveness, 88% better understood the subject, and 96% found the virtual simulator-based learning more engaging. Furthermore, the study notes improvements in students' problem-solving abilities (68%), logical reasoning (92%), and comprehension of chemical processes (94%). These findings emphasize the value of integrating neuroscience principles in chemical education, potentially benefiting both tertiary and secondary education sectors. They indicate the necessity for educational adaptation in line with interdisciplinary research in cognitive and neurological sciences. This research not only serves as a valuable resource for chemistry teachers but also sets the stage for future empirical studies exploring neuroscience's role in teacher education. The study underscores the importance of further investigation into how teachers implement neuropedagogical techniques and the effectiveness of such applications, advocating for continuous development in educational methodologies.